Effects of verapamil on pulmonary haemodynamics during hypoxaemia, at rest, and during exercise in patients with chronic obstructive pulmonary disease. - Brown, S E (1983)
The haemodynamic effects of intravenous verapamil at rest, during hypoxaemia, and during progressive exercise were evaluated in 10 patients with chronic obstructive lung disease. Verapamil produced significant decreases in the peak heart rate and systemic blood pressure during exercise but exercise capacity and pulmonary gas exchange at exhaustion were unaffected. There were no significant changes in pulmonary artery pressure or total pulmonary vascular resistance during exercise or during the breathing of either air or a hypoxic gas mixture at rest. No clinically useful benefit was found with verapamil in the dosage used in this group of patients and the value of calcium antagonists in the treatment of patients with chronic obstructive lung disease requires further clarification.